2009
DOI: 10.2176/nmc.49.430
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy and Diffusion-Weighted Imaging of Tumefactive Demyelinating Plaque -Case Report-

Abstract: Proton magnetic resonance spectroscopy, diffusion-weighted axonography, and diffusion tensor tractography in a patient with tumefactive demyelination plaque (TDP) were evaluated for differential diagnosis from glioblastoma. The findings of glutamate and glutamine elevations on magnetic resonance spectroscopy and apparent tracts within the lesion on axonography and tractography were unlikely to represent glioblastoma, and were thus useful for the preoperative diagnosis of TDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…10 Recently, 2 imaging findings of TDLs have been reported. Malhotra et al 11 found peripheral restricted diffusion on DWI in 11 of 18 patients with TDLs, while Masu et al 12 observed that intralesional fibers appeared to be a pyramidal tract on diffusion tractography in a patient with TDL. Conversely, the perilesional hyperintense FA rim that is frequently found in the perifocal edema of high-grade gliomas 13 has not been described in TDLs.…”
mentioning
confidence: 99%
“…10 Recently, 2 imaging findings of TDLs have been reported. Malhotra et al 11 found peripheral restricted diffusion on DWI in 11 of 18 patients with TDLs, while Masu et al 12 observed that intralesional fibers appeared to be a pyramidal tract on diffusion tractography in a patient with TDL. Conversely, the perilesional hyperintense FA rim that is frequently found in the perifocal edema of high-grade gliomas 13 has not been described in TDLs.…”
mentioning
confidence: 99%
“…Addition of the newer MR techniques, namely proton MR spectroscopy (MRS), diffusion tensor imaging (DTI), perfusion MRI, and susceptibility weighted imaging (SWI), have the potential to give additional information about the metabolic and microscopic structural changes within these lesions. They can thus help in the differentiation from other focal lesions (9)(10)(11)(12). This differentiation is very important as it helps to avoid an invasive brain biopsy.…”
mentioning
confidence: 99%